A method for preparing a cellulose-based hydrophobic film

CN116515149BActive Publication Date: 2026-10-27KUNMING UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310619503.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-30
Publication Date
2026-10-27
Estimated Expiration
2043-05-30

AI Technical Summary

Technical Problem

其中,纸吸管因其良好的降解性,被广泛推广,但是纸吸管在水环境中孱弱的力学性能,一直被人们所诟病

Benefits of technology

本发明利用纤维素和紫胶为原料,纤维素是地球上储量最丰富的天然聚合物,是自然界中分布最广、含量最多的一种多糖,不同尺寸的纤维素具有强烈的相互作用,能形成界面黏附作用使其形成更加坚实的三维网络结构,而且小分子量的紫胶能够填充纤维素之间的三维网状结构空隙,使复合膜具有较好的力学性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116515149B_ABST
    Figure CN116515149B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a cellulose-based hydrophobic film, which comprises the following steps: uniformly mixing two or more cellulose dispersion liquids in any proportion, extracting and filtering the mixture to obtain a filter cake, and hot-pressing the filter cake at 100 DEG C to 110 DEG C for 1 to 3 hours to obtain the hydrophobic film; and the application is based on the nanoscale entanglement, hydrogen bond connection and interface adhesion effect between two or more celluloses with different sizes, the space in the cellulose 3D network filled and interconnected by the shellac, and the cellulose straw with high mechanical strength, excellent wet stability and economy is prepared by rolling up the cellulose-based hydrophobic film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of biomass-based functional materials, specifically the field of food materials technology, and is a method for preparing a cellulose-based hydrophobic film. Background Technology

[0002] Most petrochemical plastics are not easily degraded, and the accumulation of large amounts of plastic leads to environmental pollution. Green development is an inevitable choice for human progress, and replacing plastic with paper is an important strategy to solve the current white pollution and reduce carbon emissions. Paper straws are widely used due to their good degradability; however, their weak mechanical properties in aquatic environments have been a persistent problem. Therefore, it is necessary to further improve existing technologies. From the perspective of sustainable development and durability, hydrophobic composite films with good mechanical properties and environmental friendliness are attractive materials in the catering and packaging industries. Summary of the Invention

[0003] To address the problems existing in the prior art, this invention provides a method for preparing a cellulose-based hydrophobic film. Using cellulose of different sizes and biodegradable, non-toxic shellac resin as raw materials, a hydrophobic film is prepared through a papermaking process. In this invention, cellulose dispersions of different sizes and hydrophobic shellac resin dispersions are mechanically mixed to form a uniform cellulose-shellac resin slurry. The different sizes of cellulose interact with each other, with smaller cellulose fibers filling the spaces of larger fiber networks. Strong adhesion is formed between cellulose fibers through covalent bonds, contributing to the formation of a relatively soft and tough network. Simultaneously, the composite of shellac resin and cellulose with hydrophobic segments imparts better hydrophobicity to the material, giving it stronger wet stability. The strong interaction between shellac resin and cellulose molecules results in good strength in the composite film, demonstrating the advantages of its structural design.

[0004] The technical solution of the present invention is as follows: A method for preparing a cellulose-based hydrophobic film involves mixing two or more cellulose dispersions of arbitrary proportions and different sizes, filtering the mixture using a sand core filter to obtain a filter cake, and then hot-pressing the filter cake at 100℃-110℃ for 1-3 hours using a rapid paper dryer to obtain the hydrophobic film.

[0005] The cellulose dispersion includes: nanocellulose dispersion, long cellulose dispersion, bacterial cellulose microgel, etc.

[0006] The two or more cellulose dispersions are also mixed with a biodegradable and non-toxic shellac resin dispersion, wherein the mass ratio of cellulose to shellac resin is 0.2:0.8-0.8:0.2.

[0007] The preparation method of the long fiber dispersion is as follows: Soak the long fiber pulp board in deionized water for 30-40 minutes. After soaking, the pulp board is broken down by a hydraulic pulper. Start the pulper motor to strongly disintegrate and separate the fibers in the wet state. The completely broken pulp is then pulped through a PFI refiner to determine the pulp concentration to be 10%. 30g of oven-dry pulp is pulped to obtain a pulp with a freeness of 45°SR. The long fiber pulp with a freeness of 45°SR is then mixed with water to prepare a long fiber dispersion of the required concentration (e.g., mass fraction 1-10%). The pulp concentration is then determined by oven drying and stored for later use.

[0008] The bacterial cellulose microgel preparation method is as follows: The bacterial cellulose used is commercially available molasses coconut jelly. After washing it with deionized water until the conductivity of the washing solution is consistent with that of the deionized water and TDS=0, take 1 kg of washed coconut jelly (if the volume is less than 1 L, add deionized water to 1 L), disperse it at 4800 r / min for 20 min, and the bacterial cellulose microgel is obtained. Its solid content can be measured by drying and stored for later use.

[0009] The preparation method of the nanocellulose dispersion is as follows: Based on coniferous wood fiber, the nanocellulose dispersion is prepared by TEMPO-mediated oxidation. The specific steps are as follows: 35g of coniferous wood fiber is suspended in 3500mL of deionized water containing 0.84g of TEMPO, 5.25g of sodium bromide and 328.05g of sodium hypochlorite. 0.1mol / L HCl and 0.1mol / L NaOH are added to adjust the pH to 10, and TEMPO-mediated oxidation begins. The mixture is stirred at 500rpm at room temperature. During stirring, sodium hydroxide solution is continuously added to adjust the pH until the pH is 10 and constant. The mixture is then poured into a Buchner funnel and washed with deionized water until the washing liquid is neutral. The washed nanocellulose is placed in a beaker, sealed with plastic wrap, and stored in a refrigerator at 4℃. Water is added as needed to prepare a nanocellulose dispersion of the required concentration (e.g., mass fraction 1-10%).

[0010] The shellac resin is bleached shellac resin. The preparation method of the bleached shellac resin dispersion is as follows: bleached shellac is dissolved in ethanol (95 wt.%) to prepare a bleached shellac ethanol solution with a concentration of 6.5 wt.%, stirred evenly, and the bleached shellac ethanol solution is added dropwise to deionized water at 40°C. A bleached shellac water-soluble collagen solution is prepared under the action of a powerful electric stirrer at a set speed. The ethanol is evaporated off using a rotary evaporator. The particle size of the dispersion is analyzed using a particle size analyzer, and the solid content of the bleached shellac resin dispersion is determined. It is then refrigerated for later use. Water is added as needed to prepare a bleached shellac resin dispersion of the required concentration (e.g., mass fraction 1-10%).

[0011] The cellulose-based hydrophobic film prepared by the method is rolled up and bonded together at the joint with shellac ethanol solution to obtain a green and pollution-free cellulose straw.

[0012] The beneficial effects of this invention are: This invention utilizes cellulose and shellac as raw materials. Cellulose is the most abundant natural polymer on Earth and the most widely distributed and abundant polysaccharide in nature. Cellulose of different sizes has strong interactions and can form interfacial adhesion to create a more solid three-dimensional network structure. Moreover, the small molecular weight shellac can fill the gaps in the three-dimensional network structure between cellulose, giving the composite membrane better mechanical properties. Attached Figure Description

[0013] Figure 1 Images of composite membranes and composite pipettes prepared in the laboratory; Figure 2 Comparison of the mechanical properties of cellulose straws ((a) comparison of dry strength of cellulose straws, (b) and (c) comparison of wet strength of cellulose straws). Figure 3 The water absorption rate of the cellulose straw; Figure 4 The water absorption rate of the two composite cellulose straws; Figure 5 Wet strength of straws prepared from bacterial cellulose and long fiber composites; Figure 6 The graph shows a comparison of the mechanical properties of shellac-cellulose straws. (a) represents dry strength, and (b) represents wet strength. Detailed Implementation

[0014] The present invention will be further described in detail below with reference to specific embodiments, but it should be noted that the scope of protection of the present invention is not limited to these embodiments. Abbreviations BDDE: TEMPO: 2,2,6,6-tetramethylpiperidine-nitrogen-oxide; TDS: Total dissolved solids; °SR: Freezing degree. Long fiber pulp board, molasses coconut jelly, softwood fiber, and bleached shellac are all commercially available.

[0015] The paper forming dryer used in this invention was purchased from Dongguan Internes Precision Instruments Co., Ltd., model IMT-GZ01, and requires a voltage of 220V. Example 1

[0016] The specific steps for preparing a long cellulose dispersion are as follows: Soak the long fiber pulp board in deionized water for 30-40 minutes. After soaking, the pulp board is broken down by a hydraulic pulper. Start the pulper motor to strongly disintegrate and separate the fibers in the wet state. The completely broken down pulp is then pulped through a PFI refiner to determine the pulp consistency to be 10%. 30g of oven-dry pulp is then pulped to obtain a pulp with a freeness of 45°SR. Dispersions of different concentrations are prepared from the long fiber pulp with a freeness of 45°SR and stored for later use. The solid content can be determined by oven drying. Example 2

[0017] The specific steps for preparing bacterial cellulose microgels are as follows: The bacterial cellulose used was commercially available molasses coconut jelly. After washing it with deionized water until the conductivity of the washing solution was consistent with that of the deionized water and the TDS was 0, a bacterial cellulose dispersion was prepared by mechanical method: 1 kg of washed coconut jelly was taken (if the volume was less than 1 L, deionized water was added to make 1 L), and dispersed by high-speed mechanical shearing (4800 r / min) in a high-speed blender for 20 min to obtain bacterial cellulose microgel. It was refrigerated for later use, and its solid content was measured after drying. Example 3

[0018] The specific steps for preparing the nanocellulose dispersion are as follows: A nanocellulose dispersion was prepared using coniferous wood fiber as a base via TEMPO-mediated oxidation. The specific steps were as follows: 35g of coniferous wood fiber was suspended in 3500mL of deionized water containing 0.84g of TEMPO, 5.25g of sodium bromide, and 328.05g of sodium hypochlorite. The pH was adjusted to 10 by adding 0.1mol / L hydrochloric acid and 0.1mol / L NaOH solution, initiating TEMPO-mediated oxidation. The mixture was stirred at 500rpm at room temperature, and 0.1mol / L sodium hydroxide solution was continuously added during stirring to adjust the pH until it reached a constant value of 10. The mixture was then poured into a Buchner funnel and washed with deionized water until the washing solution was neutral. The washed cellulose nanofibers were placed in a beaker, and water was added or evaporated to remove moisture to prepare a dispersion of the desired concentration. The mixture was sealed with plastic wrap and stored in a refrigerator at 4°C. Example 4

[0019] The specific steps for preparing shellac resin dispersion are as follows: Bleached shellac resin was dissolved in ethanol (95 wt.%) to prepare a 6.5 wt.% bleached shellac ethanol solution. The solution was stirred until homogeneous. The bleached shellac ethanol solution was then added dropwise to deionized water at 40°C. A bleached shellac water-soluble collagen solution was prepared by stirring with a powerful electric stirrer at a set speed. The ethanol was evaporated off using a rotary evaporator. The particle size of the dispersion was analyzed using a particle size analyzer, and the solid content of the bleached shellac resin dispersion was determined. The solution was then refrigerated for later use. Bleached shellac resin dispersions of the required concentration were prepared as needed. Example 5

[0020] A method for preparing a cellulose-based hydrophobic film, the specific steps of which are as follows: (1) Take the long cellulose dispersion with a concentration of 1 wt% prepared in Example 1, the bacterial cellulose microgel prepared in Example 2, and the nanocellulose dispersion with a concentration of 1 wt% prepared in Example 3, mix them according to the mass ratio of nanocellulose:bacterial cellulose:long cellulose of 1:1:1, stir for 30 minutes with a mechanical stirrer to obtain a uniform slurry with a concentration of 0.16 wt.%. (2) The slurry obtained in step (1) is filtered through a sand core filter. The filter membrane was purchased from Shanghai Xingya Purification Materials Factory. The specifications of the mixed cellulose ester microporous filter membrane (water system) are 110mm*0.22μm. (3) The filter cake obtained in step (2) is hot-pressed at 100°C for 1 hour using a paper sheet forming dryer to obtain a cellulose film.

[0021] By changing the mass ratio of nanocellulose:bacterial cellulose:long cellulose to 1:1:2, 2:1:1, and 1:2:1, while keeping other steps and process parameters the same as in Example 5, cellulose films were prepared.

[0022] Comparative Example 1 Compared with Example 5, the three cellulose dispersions were not mixed, and the other steps and process parameters were the same as in Example 5, respectively, to prepare pure long fiber, bacterial cellulose and nanocellulose films. Example 6

[0023] A method for preparing a cellulose-based hydrophobic film, the specific steps of which are as follows: (1) Take the long cellulose dispersion with a concentration of 1 wt.% prepared in Example 1 and the nanocellulose dispersion with a concentration of 2 wt.% prepared in Example 3, mix them according to the mass ratio of long cellulose to nanocellulose of 0.75:0.25, and stir with a mechanical stirrer for 35 minutes to obtain a uniform slurry; (2) The slurry obtained in step (1) is filtered through a sand core filter. The filter membrane was purchased from Shanghai Xingya Purification Materials Factory. The specifications of the mixed cellulose ester microporous filter membrane (water system) are 110mm*0.22μm. (3) The filter cake obtained in step (2) is hot-pressed at 105°C for 2 hours using a paper sheet forming dryer to obtain a cellulose film.

[0024] Compared with Example 6, the mass ratio of long cellulose to nanocellulose was changed to (0.5:0.5) and (0.25:0.75), while other steps and process parameters were the same as in Example 6, and cellulose films were prepared. Example 7

[0025] A method for preparing a cellulose-based hydrophobic film, the specific steps of which are as follows: (1) Take the bacterial cellulose microgel prepared in Example 2 and the nanocellulose dispersion with a concentration of 1 wt.% prepared in Example 3, mix them according to the bacterial cellulose: nanocellulose mass ratio of 0.75:0.25, and stir with a mechanical stirrer for 35 minutes to obtain a uniform slurry with a concentration of 0.16 wt.%. (2) The slurry obtained in step (1) is filtered through a sand core filter. The filter membrane was purchased from Shanghai Xingya Purification Materials Factory. The specifications of the mixed cellulose ester microporous filter membrane (water system) are 110mm*0.22μm. (3) The filter cake obtained in step (2) is hot-pressed at 110°C for 3 hours using a paper sheet forming dryer to obtain a cellulose film.

[0026] Compared with Example 7, the bacterial cellulose:nanocellulose mass ratio was changed to (0.5:0.5) and (0.25:0.75), while other steps and process parameters were the same as in Example 7, and cellulose films were prepared. Example 8

[0027] A method for preparing a cellulose-based hydrophobic film, the specific steps of which are as follows: (1) Take the long cellulose dispersion with a concentration of 1 wt.% prepared in Example 1 and the bacterial cellulose microgel prepared in Example 2. Mix them according to the mass ratio of long cellulose to bacterial cellulose of 0.75:0.25 and stir with a mechanical stirrer for 40 minutes to obtain a uniform slurry with a concentration of 0.16 wt.%. (2) Add shellac resin dispersion to the uniform slurry in step (1) and mix well to obtain a slurry with a concentration of 0.16 wt.%, and the mass ratio of cellulose to shellac resin is 0.2:0.8; (3) The slurry obtained in step (2) is filtered through a sand core filter. The filter membrane was purchased from Shanghai Xingya Purification Materials Factory. The specifications of the mixed cellulose ester microporous filter membrane (water system) are 110mm*0.22μm. (4) The filter cake obtained in step (3) is hot-pressed at 110°C for 3 hours using a paper forming dryer to obtain a cellulose film.

[0028] Compared with Example 8, the amount of shellac resin added in step (2) was adjusted so that the mass ratio of cellulose to shellac resin was 0.6:0.4, 0.4:0.6, and 0.8:0.2; other steps and process parameters were the same as in Example 8, and cellulose film was prepared. Example 9

[0029] like Figure 1 The image shows a photograph of the fiber membrane and straw prepared in the laboratory. The fiber membrane obtained above was rolled up and bonded at the joint with the bleached shellac ethanol solution prepared in Example 4 to obtain a green and pollution-free cellulose straw (the concentration of the slurry can be adjusted as needed, thereby adjusting the thickness of the membrane and the straw). The thickness of each fiber membrane was measured using a paper thickness gauge produced by Beijing Instrument Factory. The thickness of 5 different points was measured and the average value was taken as the thickness of the membrane, accurate to 0.001 mm. The membrane thicknesses are shown in Table 1 below. Table 1 Thickness of Composite Membrane Example 10

[0030] The straws prepared in Example 9 were subjected to performance tests, including mechanical properties and moisture stability. (1) The straws obtained in Example 5 and Comparative Example 1 were tested for mechanical properties. Pure long cellulose straws, pure bacterial cellulose straws, and pure nanocellulose straws were used as blank controls. All straws were uniformly cut to a size of 10mm×50mm, and the thickness was measured with a thickness gauge. The original gauge length between the two clamps was measured with a vernier caliper. The samples were subjected to tensile testing using a UTM2502 electronic universal testing machine to determine their dry strength. Three parallel samples were then prepared, soaked in water for 24 hours, and the surface moisture was wiped off. Their wet strength was then determined using the above method. The pure nanocellulose straws underwent severe deformation after soaking in water for 5 hours and did not meet the tensile requirements. A comparison chart of mechanical properties was obtained. Figure 2 (a) Comparison of dry strength of cellulose pipettes, (b) and (c) Comparison of wet strength of cellulose pipettes. It can be seen from the figure that bacterial cellulose exhibits excellent mechanical properties, while nanocellulose has poor wet strength.

[0031] (2) The straws obtained in Example 5 and Comparative Example 1 were tested for their water absorption performance. The straws were uniformly cut to a size of 10mm × 50mm, and three parallel samples were cut from each straw. The mass of each sample was measured using an analytical balance. After soaking them in water for 24 hours, the surface moisture was wiped off, and the mass was measured. The water absorption rate was calculated according to the following formula: Water absorption rate = ((BG) / G) × 100% Where G is the weight of the sample after drying, and B is the weight of the sample after saturation with moisture; the average value of three parallel samples is taken as the water absorption value of the membrane, with the water absorption of pure long fiber membrane, pure bacterial cellulose membrane, and pure nanocellulose membrane first measured as blank control values ​​for reference; the water absorption rate of the cellulose pipette is then obtained. Figure 3 Analysis still reveals that bacterial cellulose has poor water absorption and can be used as the cellulose portion of cellulose-based straws.

[0032] (3) In order to further study the complexing effect between cellulose at different scales, the water absorption rate of the cellulose straws that were combined in pairs was tested. The test method was the same as in step (2), and the water absorption rate was obtained. Figure 4 Mechanical properties are Figure 5 After analyzing and comparing the mechanical properties and water absorption rate of composite cellulose straws, the cellulose-based straws with a bacterial cellulose:long fiber ratio of 1:3 showed the best mechanical properties.

[0033] (4) The composite of shellac resin and cellulose with hydrophobic segments can impart better hydrophobicity to the material, giving it stronger wet stability. There is a relatively strong interaction between shellac resin and cellulose molecules, which makes the composite film have good strength. Therefore, the mechanical properties of the shellac-fiber straw prepared in Example 8 were tested, such as... Figure 6 With a fixed long cellulose:bacterial cellulose mass ratio of 0.75:0.25, different proportions of shellac resin were added. It was found that adding shellac did indeed improve the wet strength of the straw. The dry strength was best when the shellac addition was 0.6, and the wet strength was best when the shellac addition was 0.2. Since the straw is used in a humid environment, the wet strength is more important. By comparing the mechanical properties (dry strength and wet strength) and water absorption of the straw, the optimal composition of the cellulose-based straw was finally determined to be the mass ratio of shellac long cellulose:long cellulose:bacterial cellulose of 0.2:(0.75*0.8):(0.25*0.8)=0.2:0.6:0.2.

Claims

1. A method for preparing a cellulose-based hydrophobic film, characterized in that, The raw materials are mixed evenly, and the mixture is filtered to obtain a filter cake. The filter cake is hot-pressed at 100℃-110℃ for 1-3 hours to obtain a hydrophobic film. The raw material is composed of nanocellulose dispersion, long cellulose dispersion and bacterial cellulose microgel, and the mass ratio of nanocellulose:bacterial cellulose:long cellulose is 1:1:2, 1:2:1, and 2:1:

1. Alternatively, the raw material may consist of a long cellulose dispersion, bacterial cellulose microgel, and shellac resin dispersion, wherein the mass ratio of shellac resin to long cellulose to bacterial cellulose is 0.2:0.6:0.

2. The method for preparing the nanocellulose dispersion is as follows: 35g of coniferous wood fiber is suspended in 3500mL of deionized water containing 0.84g TEMPO, 5.25g sodium bromide and 328.05g sodium hypochlorite. The pH value is adjusted to 10, and the mixture is stirred at 500rpm at room temperature. The pH value is continuously adjusted during stirring until it is 10 and constant. The nanocellulose is washed by vacuum filtration with deionized water until the washing liquid is neutral. The washed nanocellulose is then mixed with water to prepare the nanocellulose dispersion, which is then sealed and stored at 4℃.

2. The method for preparing the cellulose-based hydrophobic film according to claim 1, characterized in that, The method for preparing the long cellulose dispersion is as follows: Soak the long fiber pulp board in deionized water for 30-40 minutes, break down the soaked pulp board, and beat it after complete breaking down to obtain a pulp with a freeness of 45°SR. Add water to the pulp with a freeness of 45°SR to prepare a long cellulose dispersion.

3. The method for preparing the cellulose-based hydrophobic film according to claim 1, characterized in that, The bacterial cellulose microgel preparation method is as follows: Wash commercially purchased molasses coconut jelly with deionized water until the conductivity of the washing solution is consistent with that of the deionized water and TDS=0. Take 1 kg of washed coconut jelly, add deionized water to 1 L, and disperse at 4800 r / min for 20 min to obtain bacterial cellulose microgel, which is then refrigerated for later use.

4. The method for preparing the cellulose-based hydrophobic film according to claim 1, characterized in that, The method for preparing the shellac resin dispersion is as follows: bleached shellac is dissolved in a 95% ethanol solution to prepare a 6.5% bleached shellac ethanol solution. The solution is stirred evenly, and then the bleached shellac ethanol solution is added dropwise to deionized water at 40°C. A water-soluble collagen solution of bleached shellac is prepared under vigorous stirring. The ethanol is evaporated off using a rotary evaporator, and water is added or evaporated to remove moisture to prepare the shellac resin dispersion, which is then refrigerated for later use.

Citation Information

Patent Citations

  • Cellulose-based transparent waterproof film with high dimensional stability and preparation method thereof

    CN111849002A